MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN 1-10 MELALUI MEDIA WADAH TELUR BAGI ANAK TUNAGRAHITA RINGAN X - AULIA Febri (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract : This study was motivated by the inability of slow learning children who have difficulty in reading the noun in SDN 01 Limau Manis, Padang. The purpose of this research is to improve the child's reading ability nouns using the enter method. Enter method is to learn to read by using the symbols using the letter cards and word cards with visual form. Therefore, researchers are interested to draw this issue so children are able to read the word correctly so that the learning process can be run well. Keyword: Media Wadah Telur; Mengenal Konsep Bilangan 1-10; Anak  Tunagrahita Ringan